The Effect Optimizing Digital Transaction Education on Customer Cross Selling at Bank Syariah Indonesia KCP Kabanjahe: English - Difi Oktavianny, Syiva; Mujiatun, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
Optimization of digital transaction users is an effort to maximize the number of digital-based transaction users. In Indonesia alone, the development of digital transactions grew much better, amounting to 1,556% in the 2017-2020 confinement, which has greatpotential to absorb the flow of digitalization. This study aims to test and analyze the effect of Digital Transaction Education Optimization on Customer Cross Selling at Bank SyariahIndonesia KCP Kabanjahe. By research method is quantitative descriptive. The design of this study is simple linear regression analysis, classical assumption test and hypothesis test. The population in this study is customers of Bank Syariah Indonesia KCP Kabanjahe amounting to 2,100 with sampling techniques using the slovin formula, amounting to 95 samples. The results of this study are Digital Transaction Education (X) has a significant effect on Customer Cross Selling (Y) at Bank Syariah Indonesia KCP Kabanjahe.